India and the responsibility to protect - Bloomfield, Alan 1975- (Rethinking Asia and international relations, 2016)
"Bloomfield charts India's profoundly ambiguous engagement with the thorny problem of protecting vulnerable persons from atrocities without fatally undermining the sovereign state system, a matter which is now substantially shaped by debates about the responsibility to protect (R2P) norm. Books about India's evolving role in world affairs and about R2P have proliferated recently, but this is the first to draw these two debates together. It examines India's historical responses to humanitarian crises, starting with the 1971 Bangladesh Liberation War, concentrating on the years 2011 and 2012 when India sat on the UN Security Council. Three serious humanitarian crises broke during its tenure - in CÃ´te d'Ivoire, Libya and Syria - which collectively sparked a ferocious debate within India. The book examines what became largely a battle over 'what sort of actor' modern India is, or should be, to determine how this contest shaped both India's responses to these humanitarian tragedies and also the wider debates about rising India's international identity. The book's findings also have important (and largely negative) implications for the broader effort to make R2P a recognised and actionable international norm."--Provided by publisher.